Técnica didáctica “Cuadro de tildes” para mejorar la tildación de los estudiantes del 4to grado “A” de primaria de la I.E N°00536 Manuel Segundo del Águila - Bazan Figueroa, Robert (2013)
The research aims to improve students tildación in fourth grade "A" Primary Level of School No. 00536 "Segundo del Aguila Manuel Velasquez" Rioja city, through teaching technique "Box tildes "The study is important because it demonstrated the effectiveness of educational technology. The central objective of the research was to demonstrate the impact of teaching technique "box Tildes" in improving the tildación of fourth graders 'A' Level Elementary Educational lnstitution No. 00536 "Manuel Segundo Eagle Velásquez- Ponazapa "city of Rioja, 2011, and the specific objectives were to analyze the tildación of students in fourth grade" A "Level Elementary, apply the didactic technique" Tildes Box "to students in fourth grade" A " Primary Level, analyze the influence of the teaching technique "Tildes Box" on tildación of students in fourth grade "A" Primary Level. \, 1 \ The tildación is supported by Ramírez, L. H. (i993) and the Royal Spanish Academy (2005), references to analyze the rules orthographic writing system, and the teaching technique "Tildes Box" is based on Llorach (1981) and Saussure (1965) analyzed the spelling from the point of view of phonology and the principies of Gestalt psychology of Biehler and Snowman analyzing the shapes of the stimuli to be present in children for leaming. The theoretical support mentioned above, we propase the following hypothesis: The teaching technique "box tildes" significantly improve tildación of students in fourth grade "A" Level Primary El No. 00536 "Manuel Segundo del Aguila Velasquez-Ponazapa" Rioja city, 2011. Methodologically, the research design was pre-experimental, with a sample of 24 students from the fourth grade "A" Level Elementary School "Eagle Second Manuel Velasquez" Rioja city in 2011. The results of the statistical analysis it was found that one accepts the central hypothesis derived from the probability table of Student's t distribution with 24 degrees of freedom and significance level 5, and the calculated and tabulated value of verifying that the calculated value is less than the tabular value left, which allows the null hypothesís to fall wíthin the rejection regían, acceptíng the research hypothesís, whereupon the applícatíon of educatíonal technology "Tildes Box "tildación has sígnífícantly improved from fourth graders.